The Integration of Artificial Intelligence in Modern Financial Management Strategies: A Review of Profit Planning, Capital Structure, and Corporate Governance - Ani Selviyanti; Muchriana Muchran (www.amertainstitute.com, 2025)
The advancement of Artificial Intelligence (AI) technology has significantly transformed the landscape of modern financial management. This article aims to examine the integration of AI across various dimensions of financial management, including fundamental concepts, profit planning, asset management, capital budgeting, capital structure, dividend policy, working capital management, debt financing, mergers, corporate governance, bankruptcy, reorganization, and liquidation. The research method employed is descriptive-qualitative with a literature review approach using both national and international scientific journals. The findings indicate that AI enhances operational efficiency, improves the accuracy of financial analysis, and supports data-driven strategic decision-making. Additionally, AI offers advantages in early bankruptcy detection and planning for corporate restructuring. However, challenges such as limited digital infrastructure, data security risks, and ethical concerns regarding algorithmic bias remain significant barriers to AI implementation. Therefore, a holistic strategy involving policy development, human resource training, and responsible technology governance is essential to maximize the sustainable benefits of AI in financial management.